PANDANGAN EMPAT MAZHAB TERHADAP KEPUTUSAN UNTUK MENJUAL DAN TUKAR GULING HARTA WAKAF - Matlaul Irfan (AL-RASYAD: JURNAL HUKUM DAN ETIKA BISNIS SYARIAH, 2023)
When a waqf object has been handed over to the nazir, at that time the waqf object has moved to belong to the people, the people have the absolute right to benefit from the object being donated. Changing the status of a waqf object from private property to public property complicates the legal status of the waqf object when the waqf is about to change its status, often a waqf object loses the benefits of the initial intention when it was first waqf due to the surrounding conditions or circumstances so that it no longer functions optimally it is even seen that its existence causes harm in that place, with such conditions the community takes the initiative through an official agency selling it or swapping it which requires that the waqf is not as full of benefits as it was at the time of the initial contract. This has become a new legal phenomenon because the sale and purchase of waqf objects or swaps do not have textual references in the Qur'an and Hadith.